Appearance of New Oscillations (Named Oscillations I and J) during Reduction of H2O2 on Platinum Electrode. Issue 9 (26th July 2017) - Mukouyama, Yoshiharu; Kawasaki, Hirokazu; Hara, Daisuke; Yamada, Yuri; Nakanishi, Shuji
Abstract : The reduction of H2 O2 on Pt electrodes in H2 SO4 solution shows various types of electrochemical oscillations, named sequentially from A to H, as has been reported previously. One of them, oscillation H, appears when Na2 SO4 or K2 SO4 is added to the acidic solution. In the presence of the cation dissociated from the salt, Na + or K +, the pH at the electrode surface becomes basic during the H2 O2 reduction, leading to the appearance of oscillation H. This present work demonstrates that new types of oscillations, named oscillations I and J, are also induced by the pH increase due to the cation. In contrast to oscillation H, oscillations I and J also appear when the H2 O2 reduction occurs on Pt electrodes in NaOH solution. They are caused by an N-shaped negative differential resistance (N-NDR) induced by the formation of under-potential deposited H. Oscillation I appears in the potential region of the N-NDR, whereas oscillation J appears at potentials more negative than the N-NDR region, i.e., at potentials where hydrogen evolution reaction occurs. Detailed studies reveal that oscillations I and J are classified into an N-NDR and a coupled N-NDR (CN-NDR) oscillator, respectively.